PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE GQGA (GIVING QUESTION AND GETTING ANSWER) TERHADAP HASIL BELAJAR MATEMATIKA - Setiani Mutia, Ana; Ratih Purnama Pertiwi; Resti Septikasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the GQGA Type Active Learning Strategy on the Mathematics Learning Outcomes of fifth-grade students of MI NU Sumedang Sari on the material of plane figures and the volume of cuboids and cubes. The method used is an experiment with a one-group pretest-posttest design. The research sample consisted of 17 students selected using a simple random sampling technique. Learning begins with giving a pretest to determine students' initial abilities. Next, learning applies the GQGA type active learning strategy involving two cards. The first card contains questions and the second card contains answers and the learning process in real-time. After learning, students are given a posttest to determine the improvement in learning outcomes. Data analysis was carried out by applying a one-sample t-test to determine student learning outcomes and a paired sample t-test to determine the influence in the study. The results showed that the average pretest score of students was 44.12, while the average posttest score was 84.41. The paired sample t-test produces a significance value of 0.000 < 0.05, which means (sig value = 0.000 < 0.05), so H0 is rejected and Ha is accepted, which means there is an influence in the use of the GQGA Type Active Learning strategy.